Analisis informasi laporan arus kas sebagai alat ukur kinerja keuangan PT. Kalbe Farma Tbk Periode 2019-2022 - Andini Setia Ningrum; Latjandu, Lady Diana (Manajemen Bisnis dan Keuangan Korporat, 2024)
This study aims to determine the company's financial performance in the 2019-2022 period with measuring instruments for cash flow ratio analysis and common size analysis. This research uses a descriptive approach. The analysis used is cash flow ratio analysis and common size analysis. The results of the study using cash flow ratio analysis showed good results because there were three ratios that met the standards, namely the Fund Flow Coverage (CAD) ratio, the Cash Coverage Against Interest (CKB) ratio and the Capital Expenditure (PM) ratio, but besides that there were three ratio values that met the standards in the Cash Coverage Against Current Debt (CKHL) ratio, namely the 2019-2021 period, and one ratio value that met the standards in the Operating Cash Flow (AKO) ratio, namely the 2020 period. Common Size analysis of the largest use of cash flow in Investment activities in the 2019 period, which amounted to 15.89% which was used for the acquisition of assets and other cash expenditures from investment activities. From these results it can be concluded that the financial performance of PT Kalbe Farma Tbk for the 2019-2022 period is good.